2010
DOI: 10.1007/s10584-010-9972-9
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous perception of changes in climate variability and its relationship with agriculture in a Zoque community of Chiapas, Mexico

Abstract: perceptions, climate knowledge, changes in climate variability , chichón Volcano, Zoque indigenous,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(24 citation statements)
references
References 33 publications
1
21
0
2
Order By: Relevance
“…In studies such as ARIZPE and SÁNCHEZ-CORTÉS & CHAVERO (2011), where gender and geographical location were the predictors of CVC, respondents' education and occupation were the predictors of CVC in the present study. Generally, respondents with different socioeconomic background aptly perceived that CVC influences one's decision to remove, or clear, the forest for other purposes.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In studies such as ARIZPE and SÁNCHEZ-CORTÉS & CHAVERO (2011), where gender and geographical location were the predictors of CVC, respondents' education and occupation were the predictors of CVC in the present study. Generally, respondents with different socioeconomic background aptly perceived that CVC influences one's decision to remove, or clear, the forest for other purposes.…”
Section: Discussionmentioning
confidence: 51%
“…Meanwhile, the majority of the study participants variously depend on the forest for their livelihood activities and income (WORLD BANK, 2000;SCHERL ET AL., 2004;USAID, 2006;ANDERSON ET AL., 2006). Our study findings report that farming is the economic activity mostly affected by changes in climate: CVC made farming activities non-lucrative through decreased amount of rainfall and increasing temperature (WORLD BANK, 2017;MACCHI ET AL., 2014;SÁNCHEZ-CORTÉS & CHAVERO, 2011;OWUSU ET AL., 2008;LOBELL & FIELD, 2007;UNDP, 2007). This problem confirms earlier reports that, as a world-wide problem, CVC represents a significant threat and challenge to peoples' livelihoods (WORLD BANK, 2017;IPCC, 2014;OLSSON ET AL., 2014;FAO, 2009;ATHULA & SCARBOROUGH, 2011;CODJOE & OWUSU, 2011;DAMPTEY & MENSAH, 2008;NELSON & AGBEY, 2005), and also changes, or disrupts, livelihood patterns among community members from agriculture to non-agricultural activities (MACCHI & ICIMOD TEAM, 2010;LAMMEL ET AL., 2008;STIGTER ET AL., 2005;RSAS, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For Lee, (2014) most research emphasizes the disaster as a risk exposure to certain phenomenon and evaluation of 5 biophysical vulnerability. However, in recent decades, a growing number of research disagrees with this approach, considering the disaster as a means of social construction (Cardona, 2003;Simelton et al, 2009;Sánchez-Cortés and Chavero, 2010;Antwi-Agyei et al, 2012). In these studies, it is shown that social factors amplify the effects of disasters related to extremes events.…”
Section: Introductionmentioning
confidence: 99%
“…People adopting livelihood options based on direct utilization of natural resources are affected more and their perceptions might be different and accurate than those following modern lifestyles. It is claimed that the indigenous knowledge can be better applied for the assessments of climate change [5][6][7] and indigenous people can better respond climate change [8][9][10]. The indigenous knowledge is also acknowledged for its crucial role in further advancing the understanding of scientific knowledge of climate change [11,12].…”
Section: Introductionmentioning
confidence: 99%